Pemenuhan Hak Khusus Tenaga Kerja Wanita di PT Bank Tabungan Negara (Persero) Kantor Cabang Solo - Imelda Rosaria Rita Damayanti; Sapto Hermawan; Rosita Candrakirana (International Forum of Researchers and Lecturers, 2024)
This study aims to determine the implementation of special rights for women workers at PT Bank Tabungan Negara (Persero) Tbk Solo Branch Office. The type of legal research used is empirical juridical legal research which is descriptive in nature using a statute approach. The type of legal material used is primary legal material and secondary legal material. The legal material collection technique used is indept interview (in-depth interview) and literature study while the legal material analysis technique used is the deduction method. The results of this study indicate that the implementation of the fulfillment of special rights for female workers at PT Bank Tabungan Negara (Persero) Tbk Solo Branch Office based on applicable laws and regulations has not been fully fulfilled. Menstrual leave has not been specifically regulated in the employment agreement between the Company and female workers. The conclusion was obtained from interviews with female workers at PT Bank Tabungan Negara (Persero) Tbk Solo Branch Office.